1990
DOI: 10.1159/000132972
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the Philadelphia chromosome in interphase nuclei

Abstract: Double fluorescence in situ hybridization was used to detect Philadelphia (Ph) chromosomes in interphase nuclei and metaphases of patients with chronic myeloid leukemia. Application of cosmid probes for 3’ ABL and 5’ BCR sequences gave better results than libraries for chromosomes 9 and 22. The present approach may provide an alternative method for monitoring minimal residual disease in Ph+ CML patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
1
1

Year Published

1991
1991
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(65 citation statements)
references
References 2 publications
1
62
1
1
Order By: Relevance
“…All details concerning pre-treatment of slides, clonogenic cells produced and the frequencies of either early or late CAFC displayed a similar distribution over the various hybridization, washing and immunochemical detection were as reported. 32 The probes used were: (1) Cos-ABL-18, a 40-kb fragment containing the 3′ coding region of the human abl gene; and (2) Cos-bcr-51 containing a 35.5-kb fragment rep- Table 1 Mean representing the coincidence of a red and green signal. In contained fewer signals were not scored as Ph + or Ph − , but bution.…”
Section: Enrichment Of Cd34-positive Progenitor Cells Stromal Feedersmentioning
confidence: 99%
“…All details concerning pre-treatment of slides, clonogenic cells produced and the frequencies of either early or late CAFC displayed a similar distribution over the various hybridization, washing and immunochemical detection were as reported. 32 The probes used were: (1) Cos-ABL-18, a 40-kb fragment containing the 3′ coding region of the human abl gene; and (2) Cos-bcr-51 containing a 35.5-kb fragment rep- Table 1 Mean representing the coincidence of a red and green signal. In contained fewer signals were not scored as Ph + or Ph − , but bution.…”
Section: Enrichment Of Cd34-positive Progenitor Cells Stromal Feedersmentioning
confidence: 99%
“…In certain diagnostic applications, such as the detection of trisomy 21, small probes are more informative than painting of whole chromosomes, because the more focal signals are easier to quantitate [48,160]. Furthermore, Single probes flanking or spanning a chromosomal breakpoint can be used to detect a diagnostically important breaking event [161][162][163] or to characterize further a breakpoint region [11,164,165]. An example of a breakpoint in the short arm of chromosome 11 from a Potter's facies Syndrome patient was previously reported and is shown in Figure IB.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…An example of a breakpoint in the short arm of chromosome 11 from a Potter's facies Syndrome patient was previously reported and is shown in Figure IB. This approach seems particularly useful in analyzing specific translocations in blood cell tumors [162,163,165]. The details, implications, and prospects of this application of nonisotopic in situ hybridization are reviewed elsewhere in this Journal [3].…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…FISH studies of interphase and metaphase cells using digoxygenin-labelled 5Ј BCR (BCRH1), and biotin-labelled 3Ј ABL (cosABL8) cosmid probes showed signal patterns consistent with this finding. Using methods previously described, 6 about one-third of cells (95/274 interphase; 26/72 metaphase) showed four distinct and separate fluorescent signals, two red and two green, indicating that those cells lacked the BCR-ABL hybrid gene (Figure 2a). Karyotype studies in September 1995 showed an increase in the proportion of Ph-negative cells to 84% (16/19), whereas FISH studies showed approximately equal numbers of BCR-ABL-positive (89) and -negative (93) interphase cells.…”
Section: Cytogenetic and Fish Analysesmentioning
confidence: 98%